Mattoana Bola sebagai Identitas Sosiokultural Masyarakat di Desa Bulutellue Kabupaten Sinjai - Abdul Rahman (PT. PENERBIT TIGA MUTIARA, 2024)
Entering the modern era, the people of Bulutellue Village still maintain a tradition, namely the mattoana bola celebration. This research aims to elaborate on the mattoana bola celebration as a sociocultural identity of the Bulutellue Village community. This research applies qualitative research methods. Data was collected through literature review and field research. Field data was collected by conducting participant observation and in-depth interviews with 9 people. Data analysis was carried out by applying the Miles and Huberman technique, namely data collection, data reduction, data presentation and drawing conclusions. The results of the research show that: (1) the mattoana bola celebration is carried out by small families who have successfully built a house and lived in it for approximately three years in a healthy condition and with sufficient sustenance. The mattoana bola celebration is an expression of gratitude to Allah by carrying out several stages, including mattanra esso, maddareheng, massolong bola, mabbarasanji, and mabbaca doang salama. (2) the implementation of the mattoana bola celebration has an important meaning for the people of Bulutellue Village because it contains several values, namely, the value of mutual cooperation, the value of togetherness, religious values, and the value of obedience to leaders.